Peralihan Hak AdSense YouTube sebagai Harta Warisan - Mutiara Banjarianty Sundari Syahputeri (Lembaga Yasin AlSys, 2026)
Although digital assets have received attention in various previous studies, research that specifically discusses the transfer of rights to sustainable digital income, such as YouTube AdSense, remains limited. This study aims to analyze the legal consequences of YouTube AdSense as inherited property and to formulate a mechanism for transferring its rights to heirs under Indonesian positive law. This study used a normative legal approach with statutory and conceptual approaches. The legal materials used included primary, secondary, and tertiary legal materials, which were analyzed qualitatively. The results showed that YouTube AdSense qualifies as intangible movable property (immateriële goederen) under Article 499 of the Indonesian Civil Code and constitutes an economic right over video content protected by copyright. Thus, this right is automatically transferred to the heirs as part of the estate based on the principle of universal succession (successio ex lege). The conclusion of this study affirms that the inheritance of YouTube AdSense gives rise to a right to royalties as well as an obligation of transparent management for the heirs. Its transfer mechanism requires proof of heir status, administrative verification with the platform, and joint management of the account. These findings provide a theoretical contribution to the development of inheritance law literature related to digital assets as well as practical implications for notaries and policymakers in formulating digital inheritance regulations. Keywords: YouTube AdSense; Digital Inheritance; Digital Assets; Transfer of Rights; Indonesian Inheritance Law